Hopelessness Experience among Stroke Survivor in Semarang - Sawab Sawab; Moch. Bahrudin; Novy Helena Catharina Daulima (Jurnal Ners, 2015)
Introduction: Hopelessness was a negative feelings about goal achievement and powerlessness feeling against an expectation. Hopelessness in stroke survivors can occur due to prolonged disability and neurologic defi cit. This condition can lead to emotional and mental disorders even a suicide action. Therefore, it was a need to explore hopelessness experience in stroke survivors.Methods: This study was a qualitative descriptive phenomenology with 6 participants.Results: 7 themes were revealed in this study, (1) Physical changes as a response on hopelessness, (2) Loss response as a hopelessness stressor, (3) Dysfunction of the family process, (4) Loss of meaning of life, (5) Self support and motivation as a coping resource against hopelessness, (6) The spiritual meaning behind hopelessness, (7) Can go through a better life.Conclusion: This study suggests to develop a nursing care standards in hopelessness, encourage a family support and family psychoeducation for stroke survivors.